Analisa dan Rancangan UI/UX Aplikasi Reservasi Pasien Praktik Dokter Menggunakan Metode Desain Thinking - Setiawan, Muhammad Rizky; Prasetyo, Arfhan (Journal of Information System, Informatics and Computing, 2024)
The development of information technology today makes it easier for humans to get information from applications and other means. So that applications can be a solution to the problem of time to be more efficient. The doctor's reservation process is still done manually, which requires patients to come directly to the practice location. This research aims to make it easier for patients to make reservations through designing mobile application designs that focus on user needs. The research method used by researchers is Design Thinking to match the UI/UX aspects. Researchers use the Design Thinking stage to ensure that the designed solution is in accordance with user needs. At the testing stage, researchers used the System Usability Scale (SUS) to determine the usability of application design when used by users. The result of the research is a mobile application design that can be used by patients with doctor reservation facilities and can be used by patients at any time.With the design of the application the author hopes that it can be developed into an application that can be used in the future. Because the application will make it easier for patients if they want to make reservations from anywhere